Changes in tribological and antibacterial properties of poly(methyl methacrylate)-based 3D-printed intra-oral appliances by incorporating nanodiamonds. (October 2020) - Mangal, Utkarsh; Min, You Jin; Seo, Ji-Young; Kim, Dae-Eun; Cha, Jung-Yul; Lee, Kee-Joon; Kwon, Jae-Sung; Choi, Sung-Hwan
Abstract: It is essential for 3D-printed intra-oral appliances to be able to withstand the mechanical and microbial insult existent in the harsh environment of the oral cavity. Poly(methyl methacrylate) (PMMA)-based appliances are widely used in dentistry. Hence, the present study aimed to evaluate the role of nanodiamonds (NDs) as fillers to enhance the resistance to friction and wear. Using a solution-based mixing technique, 0.1 wt% ND was incorporated into the PMMA, and specimens were 3D-printed for tribological and bacterial analysis. The control specimens without ND fillers were tested against specimens with both amine-functionalized NDs (A-ND) and pure non-functionalized NDs (ND). The surface hardness test revealed a statistically significant increase in the Vickers micro-hardness ( p  < 0.001) in the nanocomposite groups. There was a significant reduction in the coefficient of friction (COF) ( p  < 0.01) in both the ND and A-ND nanocomposites compared to the stainless steel (SS) counter surfaces. However, for titanium (Ti)-based specimens, the COF of the control group was similar to that of A-ND but lower than that of ND. The wear resistance evaluation revealed that both the ND and A-ND groups displayed enhanced resistance to surface loss in comparison to the controls for both SS and Ti counter-surfaces ( p  < 0.001). Furthermore, both A-ND and ND exhibited significantly enhanced resistance to the formation of Streptococcus mutans biofilms after 48 h ( p  < 0.01) compared to the control group. Hence, we concluded that the addition of 0.1 wt% ND in the PMMA-based resin for 3D printing resulted in significant improvement in properties such as COF, wear resistance, and resistance to S. mutans, without any notable impact associated with the functionalization of the NDs. Graphical abstract: Image 1 Highlights: Nanodiamond (ND) fillers enhance the resistance to friction. Nanosized fillers exhibit significant reinforcement effects on the hardness and wear resistance of the composites. PMMA-based resin containing 0.1 wt% ND shows improved resistance to Streptococcus mutans colonization. ND-incorporated PMMA materials can be used in 3D-printed intra-oral appliances.